Language Error in Public Spaces: Evidence from Palu City - Suparni, Suparni (Pulchra Lingua: A Journal of Language Study, Literature & Linguistics, 2024)
This study examines errors in Indonesian usage in public spaces in Palu City, focusing on non-standard language, grammatical inaccuracies, spelling, and punctuation. Using a qualitative descriptive method, data were collected through observation and documentation, analyzed with Krippendorf's content analysis model. The findings reveal 69 errors, including 40 prefix, 15 suffix, 10 preposition, 3 title, and 1 word usage errors. The most frequent issue was incorrect "di" prefix usage. Errors stem from two main factors: lack of awareness of language rules and low linguistic knowledge in the community. These mistakes risk negatively influencing the younger generation by normalizing incorrect usage. The study emphasizes the need for increased education and socialization to promote proper Indonesian language use, fostering greater awareness and adherence to linguistic standards.